A short course of tofacitinib sustains the immunoregulatory effect of CTLA4‐Ig in the presence of inflammatory cytokines and promotes long‐term survival of murine cardiac allografts. Issue 8 (18th February 2021) - Iglesias, Marcos; Khalifian, Saami; Oh, Byoung C.; Zhang, Yichuan; Miller, Devin; Beck, Sarah; Brandacher, Gerald; Raimondi, Giorgio
Abstract : Costimulation blockade‐based regimens are a promising strategy for management of transplant recipients. However, maintenance immunosuppression via CTLA4‐Ig monotherapy is characterized by high frequency of rejection episodes. Recent evidence suggests that inflammatory cytokines contribute to alloreactive T cell activation in a CD28‐independent manner, a reasonable contributor to the limited efficacy of CTLA4‐Ig. In this study, we investigated the possible synergism of a combined short‐term inhibition of cytokine signaling and CD28 engagement on the modulation of rejection. Our results demonstrate that the JAK/STAT inhibitor tofacitinib restored the immunomodulatory effect of CTLA4‐Ig on mouse alloreactive T cells in the presence of inflammatory cytokines. Tofacitinib exposure conferred dendritic cells with a tolerogenic phenotype reducing their cytokine secretion and costimulatory molecules expression. JAK inhibition also directly affected T cell activation. In vivo, the combination of CTLA4‐Ig and tofacitinib induced long‐term survival of heart allografts and, importantly, it was equally effective when using grafts subjected to prolonged ischemia. Transplant survival correlated with a reduction in effector T cells and intragraft accumulation of regulatory T cells. Collectively, our studies demonstrate a powerful synergism between CTLA4‐Ig and tofacitinib and suggest their combined use is a promising strategy for improved management of transplanted patients. Abstract : In a mouse model of heart transplantation, tofacitinib controls costimulation‐independent T cell activation and synergizes with CTLA4‐Ig to promote long‐term survival of grafts subjected to prolonged ischemia.